The LINC Between Mechanical Forces and Chromatin - Lityagina, Olga; Dobreva, Gergana (Frontiers in Physiology, 2021)
The heart continually senses and responds to mechanical stimuli that balance cardiac structure and activity. Tensile forces, compressive forces and shear stress are sensed by the different cardiac cell types and converted into signals instructing proper heart morphogenesis, postnatal growth and function. Defects in mechanotransduction, the ability of cells to convert mechanical stimuli into biochemical signals, are implicated in cardiovascular disease development and progression. In this review, we summarize the current knowledge on how mechanical forces are transduced to chromatin through the tensed actomyosin cytoskeleton, the LINC (linker of nucleoskeleton and cytoskeleton) complex and the nuclear lamina. We also discuss the functional significance of the LINC complex in cardiovascular disease.